STRATEGIES FOR IMPROVING PATIENT SAFETY IN HOSPITALS - M.M.Muyassarova; S.E.Boltaboyev (Western European Studies, 2025)
Patient safety has become a top priority for healthcare organizations. A better patient safety environment is associated with a lower probability of significant complications. Training programmers is critical to promoting patient safety and minimizing misunderstandings. The quality, performance, and productivity of the healthcare industry can be dramatically improved by changing the patient safety atmosphere operating within the hospital sector. Hospitals can significantly reduce medical errors and adverse events by implementing the program and training programmers to prioritize patient safety. This will improve patient outcomes and increase efficiency and effectiveness. Creating a patient safety culture within hospitals will contribute to a higher standard of care and improved overall performance in the healthcare industry. Hospitals can identify systemic problems and implement proactive measures to prevent future incidents by creating an environment in which healthcare professionals feel comfortable reporting errors. A patient safety culture encourages collaboration and open communication among healthcare teams leading to more effective and coordinated care.
Keywords: : infection prevention; healthcare education healthcare quality; safety culture